Time Dependency of Psychotherapeutic Exchanges: The Contribution of the Theory of Dynamic Systems in Analyzing Process - Salvatore, Sergio; Tschacher, Wolfgang (Frontiers in Psychology, 2012)
This paper provides a general framework for the use of TDS in the field of psychotherapy research. Psychotherapy is inherently dynamic, namely a function of time. Consequently, the improvement of construct validity and clinical relevance of psychotherapy process research require the development of models of investigation allowing dynamic mappings of clinical exchange. Thus, the Theory of Dynamic Systems (TDS) becomes a significant theoretical and methodological reference. The paper focuses two topics. First, the main concepts of TDS are briefly introduced together with a basic typology of approaches developed within this domain. Second, we propose a repertoire of investigation strategies that can be used to capture the dynamic nature of clinical exchange. In this way we intend to highlight the feasibility and utility of strategies of analysis informed by TDS.